A prevalence study of pharyngitis and its associated factors among adults with a sore throat in three primary clinics in Selangor, Malaysia - Muthanna, Abdul Rahman (Universiti Putra Malaysia, 2021)
Introduction: Since pharyngitis in adults is one of the most common infectious diseases seen in general practitioner consultations in Malaysia, data on pharyngitis among adults concerning to its prevalence, socio-demographic, risk factors and clinical manifestations is very much lacking. This study aims to determine the prevalence of pharyngitis among adults in Sepang, Selangor, Malaysia from 2016 to 2017 and its associated demographic and risk factors. Methods: We conducted a cross-sectional study on 215 adult patients with a sore throat as the main symptom and who did not receive any antibiotic treatment within two weeks at three Malaysian primary care clinics. The researchers assessed the participants’ clinical manifestations and collected throat swabs for culture to determine the presence of group A streptococcus (GAS). Data on demographic characteristics, clinical manifestation and throat swab culture results were analyzed using chi-square test and multivariate logistic regression. Results: Pharyngitis was diagnosed in 130/215 (65%) adults with a sore throat. Only six isolates (2.8%) were identified as GAS. The overall mean age ± S.D was 36.43 ± 15.7. The majority of the participants were in the age group of 18-28 years. There were 42.3% males and 57.7% females; most participants were Malay 62.8%, followed by 30.2% Indian, 5.1% Chinese, and 1.9% other ethnicities. The most common symptom among the participants was cough 196 (91.2%), followed by rhinorrhea 161 (74.8%), tonsillar swelling or exudates 68 (31.6%), inflamed or reddish of pharynx 62 (28.8%), swollen anterior cervical lymph nodes 50 (23.3%), and fever ≥37.5°C 28 (13.0%). Conclusion: Besides, there was no significant association between pharyngitis and the demographic variables; the current findings emphasized that inflamed or reddish pharynx, tonsillar swelling or exudates were among the factors associated with pharyngitis.